Pendampingan Peningkatan Kompetensi Sumber Daya Manusia Pemilik UMKM Peyek di Desa Telang Sari - Mareta, Mareta; Trisninawati; Jemakmun; Dewi Sartika (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy but are often constrained by limited human resource competencies. This community service activity aims to improve the competency of peyek (traditional cracker) MSME owners in Telang Sari Village through training focused on product innovation, market trend understanding, and flavor variant development. The methods used include interviews, discussions, and participatory training with one business owner as the subject. The results show an increase in participants' understanding and motivation to create product innovations, such as developing new flavor variants (dried shrimp and anchovy), as well as awareness of the importance of adapting products to consumer preferences. This training positively contributes to the development of local peyek businesses and opens up insights for MSME actors to compete in a dynamic market.